Multiplex Ligation Dependent Probe Amplification Based Mutation Analysis of Dystrophin Gene in Nepalese Patients with Duchenne Muscular Dystrophy - Shrestha, Kushal; Shrestha, Smita; Khatiwada, Saroj; Acharya, Bishu; Manandhar, Sulochana; Pokharel, Rohit Kumar (Nepal Journal of Biotechnology, 2016)
Duchenne muscular dystrophy (DMD) is X-linked recessive neuromuscular disorders caused due to mutation in dystrophin gene, leading to progressive muscle weakness. This study was done to identify mutation in dystrophin gene in Nepalese patients with DMD using Multiplex Ligation Dependent Probe Amplification (MLPA) assay in Nepal. Twenty one patients from different regions of Nepal, who were clinically diagnosed as DMD were enrolled in the study. Peripheral blood samples were collected in EDTA vials, gDNA was extracted, and deletion mutation in the dystrophin gene was analysed using Multiplex Ligation Dependent Probe Amplification (MLPA) assay. Exon deletion mutation in the dystrophin gene was observed in 14 (66.6%) out of 21 DMD cases. The most common exon deletion was observed and confined in exon 7-14 and 45-53 of dystrophin gene. The location of deletion in dystrophin gene is apparently non-random with a preponderance found in the hot spot regions. Use of MLPA is useful in detecting copy number changes in DMD proband and suspected carriers in Nepal.